The Nonprofit Worker in a For-Profit World - Preston, Anne E. (Journal of Labor Economics, 1989)
This article investigates the experience of white-collar workers in nonprofit firms. The theoretical model of the nonprofit labor market suggests that workers supply labor to nonprofit organizations at lower than market wages in return for the opportunity to provide goods with positive social externalities. Average nonprofit wage differentials of approximately -0.20 and -0.05 are estimated for managers and professionals and for clerical and sales workers, respectively, in two national worker data sets. Further research is needed for more conclusive evidence concerning the possibility that the estimated differential may reflect low-quality workers selecting work in the nonprofit sector.